Human resource management : challenges and future directions - Wiesner, Retha (John Wiley & Sons Australia, Ltd., 2003)
Summary: Presents a collection of essays exploring aspects of human resource and people management that pose particular challenges to managers today. The pressing issues, controversies and trends surrounding contemporary themes in HR management are examined, and the implications for organisations, managers and their employees are discussed. This book features the work of many of the best-known researchers in HR management in Australia and New Zealand.